2013
DOI: 10.1111/srt.12120
|View full text |Cite
|
Sign up to set email alerts
|

Prototype tactile feedback system for examination by skin touch

Abstract: We successfully developed a tactile feedback system for virtual skin wrinkle simulation by means of a commercialized haptic device that provides the user with a single point of contact to feel the surface roughness of a virtual skin sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…For instance, to consider the rougher surface patches only; a threshold in roughness can be set and visualized, which can be useful in diagnosing the infected area. The reconstructed skin surfaces from a single skin image were also tested with a haptic skin imaging system that was developed by prior studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, to consider the rougher surface patches only; a threshold in roughness can be set and visualized, which can be useful in diagnosing the infected area. The reconstructed skin surfaces from a single skin image were also tested with a haptic skin imaging system that was developed by prior studies …”
Section: Resultsmentioning
confidence: 99%
“…An initial study for developing a prototype of image‐based haptic palpation was conducted by Lee et al who showed the possibility of developing a haptic palpation system by combining a stereo microscope and a commercial 3 degree of freedom haptic device. Since then, advanced haptic rendering algorithms have been developed for taking into account human touch perception integrated with vision for estimating skin surface roughness, haptic roughness estimation such that it is actually felt by dermatologists while palpating the skin surface, and globally curved skin surface reconstruction from a single skin image .…”
Section: Introductionmentioning
confidence: 99%
“…However, relying solely on visual information obtained from captured images has a limitation in providing sufficient information (roughness and hardness) on the skin surface for a dermatologist. Therefore, the use of palpation information as well as visual information through a haptic device has been steadily gaining attention . Thus, in order to utilize a haptic device to obtain palpation information, a sophisticated three‐dimensional (3D) skin surface reconstruction method should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of palpation, it adds the risks of secondary infection and damage to diseased skin. Fortunately, recent 3D skin surface reconstruction and rendering technologies have enabled haptic feedback, which is generated from image‐based skin surface imaging . This type of reconstruction technology enables remote palpation diagnoses of skin disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent 3D skin surface reconstruction and rendering technologies have enabled haptic feedback, which is generated from image-based skin surface imaging. [7][8][9][10][11][12] This type of reconstruction technology enables remote palpation diagnoses of skin disease. Therefore, precise 3D skin surface reconstruction leads to a very important and challenging study toward an ultimate solution of 3D haptic skin palpation.…”
mentioning
confidence: 99%